Long Non-coding RNAs Involved in Pathogenic Infection - Shirahama, Shintaro; Miki, Atsuko; Kaburaki, Toshikatsu; Akimitsu, Nobuyoshi (Frontiers in Genetics, 2020)
Recently developed technologies have revealed that the genomes of many organisms produce transcripts that do not encode proteins. These are called non-coding RNAs. Long non-coding RNAs (lncRNAs) are important regulators of the expression of their target genes at the levels of transcription, translation, and degradation. Multiple studies have demonstrated a role for lncRNAs in various biological responses, including pathogenic infection. Upon pathogenic infection, the expression levels of lncRNAs are dynamically altered, suggesting that lncRNAs are involved in the host immune response or propagation of pathogens. In this review, we focused on host lncRNAs that are involved in pathogenic infection. Some host lncRNAs act as host defense molecules to prevent pathogenic proliferation, while others are utilized by the pathogen to enhance the propagation of pathogens.